2011
DOI: 10.1016/j.pmrj.2010.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Hand‐held Dynamometry Correlation With the Gold Standard Isokinetic Dynamometry: A Systematic Review

Abstract: Considering hand-held dynamometry's ease of use, portability, cost, and compact size, compared with isokinetic devices this instrument can be regarded as a reliable and valid instrument for muscle strength assessment in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
458
2
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 573 publications
(511 citation statements)
references
References 38 publications
5
458
2
16
Order By: Relevance
“…2,3 In a recent meta-analysis comparing HHD with isokinetic dynamometry, authors concluded that although the HHD is a reliable and valid instrument for measuring muscle strength, validity and reliability can be compromised when testing large joints such as the hip and knee. 4 The difficulty in comparing studies involving handheld dynamometry includes the variety of types of handheld dynamometers and differences in protocol and positioning. 4 Given the difficulty of stabilizing large joints such as the knee during testing with an HHD, we chose to use a stabilization strap.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3 In a recent meta-analysis comparing HHD with isokinetic dynamometry, authors concluded that although the HHD is a reliable and valid instrument for measuring muscle strength, validity and reliability can be compromised when testing large joints such as the hip and knee. 4 The difficulty in comparing studies involving handheld dynamometry includes the variety of types of handheld dynamometers and differences in protocol and positioning. 4 Given the difficulty of stabilizing large joints such as the knee during testing with an HHD, we chose to use a stabilization strap.…”
Section: Discussionmentioning
confidence: 99%
“…4 The difficulty in comparing studies involving handheld dynamometry includes the variety of types of handheld dynamometers and differences in protocol and positioning. 4 Given the difficulty of stabilizing large joints such as the knee during testing with an HHD, we chose to use a stabilization strap. In addition, other studies have not accounted for body weight in the analysis, so it is difficult to compare our values with those reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Handheld dynamometry (HHD) provides the clinician working in a clinical setting with objective assessment results comparable to isokinetic dynamometry for shoulder strength assessment (5). Despite the established reliability and validity of a HHD, the disadvantage of its use is inaccessibility with each unit often exceeding $1,000AUD.…”
Section: Introductionmentioning
confidence: 99%